Energy and cost analysis of bottom waste cooking oil (B-WCO) based solid alcohol biofuel and supernatant waste cooking oil (S-WCO) based biodiesel - Ramin Nabizadeh; I.L. García; Zohreh Bahmani; Abbas Norouzian Baghani; Sodeh Sadjadi; Kamyar Yaghmaeian; Bahram Kamarehie; Amir Hossein Mahvi; Masud Yunesian (Heliyon)
Waste cooking oil (WCO) represents one of the most available renewable energy sources to produce solid alcohol biofuel (SABF) and biodiesel. The objective of this work is to conduct energy and cost balances for biodiesel and SABF generation from supernatant waste cooking oil (S-WCO) and bottom waste cooking oil (B-WCO) derived from catering facilities in Iran, respectively. The total energy input/output for SABF and biodiesel, respectively, were 31.738/37.180 MJ/L and 34.269/42.163 MJ/L, with the majority of the energy contribution being B-WCO/S-WCO (78.77/73.57 %), followed by machinery (19.76/18.30 %), and ethanol/methanol (0.69/7.47 %), in both cases. Renewable energy and non-renewable energy inputs for SABF and biodiesel were calculated as 25.071 MJ/L/6.667 MJ/L and 25.280 MJ/L/8.990 MJ/L of total energy input, respectively. Total cost and revenues for SABF vs. biodiesel production processes were 1.318 vs. 1.342 $/L and 5.620 vs. 2.481$/L, respectively. Gross return, net return and beneﬁt to cost ratio values for SABF vs. biodiesel were 1.449 vs. 1.548 $/L, 1.060 vs. 1.157 $/L, and 1.827 vs. 1.876, respectively. Hence, considering the energy balances of the valorization process for WCO, the population growth in cities, and the need for inexpensive and plentiful sources of renewable energy, the production of SABF and biodiesel may offer a valuable solution in developing countries.